Transcriptional regulator PRDM12 is essential for human pain perception (2015)
Pain perception has evolved as a warning mechanism to alert organisms to tissue damage and dangerous environments. In humans, however, undesirable, excessive or chronic pain is a common and major societal burden for which available medical treatments are currently suboptimal. New therapeutic options have recently been derived from studies of individuals with congenital insensitivity to pain (CIP). Here we identified 10 different homozygous mutations in PRDM12 (encoding PRDI-BF1 and RIZ homology domain-containing protein 12) in subjects with CIP from 11 families. Prdm proteins are a family of epigenetic regulators that control neural specification and neurogenesis. We determined that Prdm12 is expressed in nociceptors and their progenitors and participates in the development of sensory neurons in Xenopus embryos. Moreover, CIP-associated mutants abrogate the histone-modifying potential associated with wild-type Prdm12. Prdm12 emerges as a key factor in the orchestration of sensory neurogenesis and may hold promise as a target for new pain therapeutics. © 2015 Nature America, Inc. All rights reserved.